(untitled) (Ciencias de la Ingeniería y Aplicadas, 2021)
The present work constitutes a bibliographic review carried out on stepper motors, where the main concepts associated with this machine, its operation, construction characteristics and the most important applications within the robotics industry are defined. Likewise, the classification of these machines is shown according to the two main categories that currently exist, which are permanent magnet motors and variable reluctance motors. Reference is also made to the variant that combines both categories, which are called hybrids as they present the best characteristics of the variable reluctance and permanent magnet ones, which are built with multi-toothed stators and a permanent magnet rotor. The main applications include its use in packaging, assembly, rotating tables and robotics equipment, among others.